Working or Ngayah? Work-Life Balance Among Balinese Women Through the Lens of Boundary Theory - Putu Ayu Athisa Indianisiswi; Tience Debora Valentina (Buletin Psikologi, 2026)
Bali's cultural dynamics require each individual to balance domestic, economic, and cultural roles adaptively. The research subjects, married Balinese women with jobs, face the challenge of balancing work with family and cultural roles to achieve work-life balance. This literature review aimed to examine Balinese women’s work-life balance from the perspective of work/family border theory. The findings reveal that the roles of Balinese women in their families, local culture, and work lead to different flexibilities and permeabilities within each family. Balinese women can maintain work-life balance by effectively controlling the permeability and flexibility of their work and family borders. This indicates that in addition to the women’s efforts, the support of family and colleagues significantly influences work-life balance, especially in the performance of ngayah. This research contributes to the understanding of Balinese women's work-life balance and can serve as a source of knowledge for stakeholders to support the work-life balance of working Balinese women.